Edible oleogels : structure and health implications - Marangoni, Alejandro G., 1965-; Garti, Nissim, 1945- (Elsevier Ltd. : Academic Press and AOCS Press, 2018)
Edible Oleogels, Structure and Health Implications, Second Edition presents a novel strategy on how to eliminate trans fats from our diets. Topics covered include how to avoid excessive amounts of saturated fat by structuring oil to make it behave like crystalline fat and how to develop trans fat free, low saturate, functional shortenings for the food industry. The major approach to form these materials is covered, helping manufacturers incorporate specific molecules (polymers, amphiphiles, waxes) into oil components. As such, this an ideal resource for those in product development and anyone interested in understanding the role of trans and saturated fats in health and nutrition. In an effort to provide alternatives to trans and saturated fats, scientists have been busy modifying the physical properties of oils to resemble those of fats. Many food products requiring a specific texture and rheology can be made with these novel oil-based materials without causing significant changes to final product quality. Hence, this book provides a valuable resource on new advancements.